Modeling the distribution of a wide‐ranging invasive species using the sampling efforts of expert and citizen scientists. Issue 19 (19th September 2019) - Roy‐Dufresne, Emilie; Saltré, Frédérik; Cooke, Brian D.; Mellin, Camille; Mutze, Greg; Cox, Tarnya; Fordham, Damien A.
Abstract: In its invasive range in Australia, the European rabbit threatens the persistence of native flora and fauna and damages agricultural production. Understanding its distribution and ecological niche is critical for developing management plans to reduce populations and avoid further biodiversity and economic losses. We developed an ensemble of species distribution models (SDMs) to determine the geographic range limits and habitat suitability of the rabbit in Australia. We examined the advantage of incorporating data collected by citizens (separately and jointly with expert data) and explored issues of spatial biases in occurrence data by implementing different approaches to generate pseudo‐absences. We evaluated the skill of our model using three approaches: cross‐validation, out‐of‐region validation, and evaluation of the covariate response curves according to expert knowledge of rabbit ecology. Combining citizen and expert occurrence data improved model skill based on cross‐validation, spatially reproduced important aspects of rabbit ecology, and reduced the need to extrapolate results beyond the studied areas. Our ensemble model projects that rabbits are distributed across approximately two thirds of Australia. Annual maximum temperatures >25°C and annual minimum temperatures >10°C define, respectively, the southern and northern most range limits of its distribution. In the arid and central regions, close access to permanent water (≤~ 0.4 km) and reduced clay soil composition (~20%–50%) were the major factors influencing the probability of occurrence of rabbits. Synthesis and applications . Our results show that citizen science data can play an important role in managing invasive species by providing missing information on occurrences in regions not surveyed by experts because of logistics or financial constraints. The additional sampling effort provided by citizens can improve the capacity of SDMs to capture important elements of a species ecological niche, improving the capacity of statistical models to accurately predict the geographic range of invasive species. Abstract : We developed an ensemble of species distribution models (SDMs) to determine the geographical range limits and habitat suitability of an important invasive species, the European rabbit, in Australia. We examined the advantage of incorporating data collected by citizens (separately and jointly with expert data) and explored issues of spatial biases in occurrence data by implementing different approaches to generate pseudo‐absences. Our results show that citizen science data can play an important role in managing invasive species by providing missing information on occurrences in regions not surveyed by experts, improving the capacity of SDMs to capture important elements of a species ecological niche and therefore their ability to predict the structure of the geographic range of invasive species.